A case report on a sporadic retroperitoneal malignant peripheral nerve sheath tumour mimicking a pelvic abscess - Vidyanendh, Vijayalakshmi; Damodaran, Arun; Karunakaran, Amilthan; Arumugam, Shri Ranjani (International Surgery Journal, 2019)
Soft tissue sarcomas (STS) are a diverse group of neoplasms with about 60 subtypes arising from a variety of anatomical structures across all age groups. The diagnosis of STS can prove to be challenging as it mimics a variety of non malignant conditions. Here we present one such case of a sporadic MPNST which was operated on with the main differential diagnosis of a Pelvic Abscess. Hence though STS is rare in general population it should always be kept in mind in cases of doubtful and confusing presentations.